Backward joint model and dynamic prediction of survival with multivariate longitudinal data. (20th May 2021) - Shen, Fan; Li, Liang
Abstract : An important approach to dynamic prediction of time‐to‐event outcomes using longitudinal data is based on modeling the joint distribution of longitudinal and time‐to‐event data. The widely used joint model for this purpose is the shared random effect model. Presumably, adding more longitudinal predictors improves the predictive accuracy. However, the shared random effect model can be computationally difficult or prohibitive when a large number of longitudinal variables are used. In this paper, we study an alternative way of modeling the joint distribution of longitudinal and time‐to‐event data. Under this formulation, the log‐likelihood involves no more than one‐dimensional integration, regardless of the number of longitudinal variables in the model. Therefore, this model is particularly suitable in dynamic prediction problems with large number of longitudinal predictors. The model fitting can be implemented with tractable and stable computation by using a combination of pseudo maximum likelihood estimation, Expectation‐Maximization algorithm, and convex optimization. We evaluate the proposed methodology and its predictive accuracy with varying number of longitudinal variables using simulations and data from a primary biliary cirrhosis study.